Evaluation of New Insecticides Against Diamond Back Moth, Plutella xylostella (L.) on Red Cabbage - Patra, B.; Das, B. C.; Alam, Sk. F.; Dhote, V.; Patra, S.; Chatterjee, M. L.; Samanta, A. (International Journal of Bio-resource and Stress Management, 2015)
In order to study the effectiveness of rynaxypyr 18.5 SC, flubendiamide 20 WG, spinetoram 12 SC, dinotefuran 20 SG, indoxacarb 14.5 SC, novaluron 10 EC and mixed formulation of indoxacarb 4.5% and novaluron 5.25% against Plutella xylostella, a field trial was conducted during rabi season in 2010-11 at Instructional Farm, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India. Rynaxypyr 18.5 SC @ 30 g a.i. ha-1 was found to be the most effective in reducing larval population followed by flubendiamide 20 WG @ 40 g a.i. ha-1 and spinetoram 12 SC @ 50 g a.i. ha-1. To determine LC50 values and relative toxicity of these insecticides against the target insect, leaf dip bioassay method was followed. Based on LC50 values, rynaxypyr was the most toxic insecticide followed by flubendiamide, spinetoram, indoxacarb and dinotefuran. Rynaxypyr showed highest acute toxicity with the lowest LC50 value (6.32 ppm), whereas novaluron showed lowest acute toxicity with the highest LC50 value (208.6 ppm).